Fiesta en La Mision. Articulating identity among ruins, rodeos and calabaceado dances (Raíces: Revista de Ciencias Sociales y Políticas, 2024)
The selected photographs are the result of the ethnographic observation record of the XL Fiesta in La Misión, carried out on June 25 and 26, 2022. These images illustrate the various cultural references and practices, which are intertwined to build the local identity of the population of La Misión, in the state of Baja California, Mexico. Thus, through the annual execution of the festival, which includes rodeos, horse riding and calabaceado dances, the residents of La Misión promote a local idea of how Mexican culture is lived on the northern border of the country.
Keywords: Heritage; identity; memory; rodeo; pumpkin dances